Quantifying the effects of scale and heterogeneity on the confined strength of micro-defected rocks. (February 2018) - Stavrou, A.; Murphy, W.
Abstract: A numerical study was performed to develop a framework for estimating the confined strength of rock blocks considering scale effects and in-situ heterogeneity (i.e. intensity of structural microdefects and degree of weathering). Grain boundary models using the Voronoi tessellation scheme within UDEC have been used to simulate the results of small (lab) and large (field) scale compression (unconfined and triaxial) and indirect tensile (Brazilian) tests on a series of progressively larger in size and degrading in quality numerical specimens. Accordingly, relationships that link rock block strength with its volume and in-situ condition were developed for the preliminary estimation of scaled Mohr-Coulomb and Hoek-Brown parameters. The results from the scaling analysis generally suggest that cohesion decreases with both increasing scale and degrading sample condition in a manner similar to the scale/condition dependant reduction of uniaxial compression strength (UCS), while the friction angle shows only minor variation with no apparent trend. The measured peak confined strength values were also fitted to the Generalized Hoek-Brown criterion and a new block-scale Geological Strength Index parameter is introduced named micro GSI (mGSI) which was also linked to the scale/condition dependant reduction of UCS. By using the proposed linear and non-linear approaches, once the UCS reduction due to scaling effects is known, the confined strength of rock blocks could be then defined and can be used to carry out preliminary rock engineering calculations and to run discontinuum numerical models in which rock blocks are simulated explicitly.